Efficiency Considering Credit Risk in Banking Industry, Using Two-stage DEA - Ghafoorian, Hadi; ., NikIntan Norhan; ., Mohammed Ndaliman Abubakar; ., Fazel Mohammadi Nodeh (Journal of Social and Development Sciences, 2013)
The increased competition in the banking industry and banks’ efforts to participate in new markets has affected bank performance and credit risk. Their presence in new markets and strong competition from other competitors today makes them face more uncertain situation. Given the importance of this issue, there are few studies about the efficiency calculated with regard to credit risk. Banking literature on this subject is poor. This paper introduces two-stage data envelopment analysis technique for estimation of their efficiency with regard to credit risk, its output and inputs in the first and second stage. Non-performing loans is output to proxy credit risk.